Juvenile idiopathic inflammatory myopathies: the value of magnetic resonance imaging in the detection of muscle involvement - Hilário, Maria Odete Esteves; Yamashita, Hélio; Lutti, Daniela; Len, Cláudio; Terreri, Maria Teresa; Lederman, Henrique (São Paulo Medical Journal, 2000)
CONTEXT: One of the major current challenges related to juvenile idiopathic inflammatory myopathy is the search for highly sensitive and specific non-invasive methods for diagnosis as well as for follow-up. OBJECTIVES: The aim of our study was to describe typical magnetic resonance imaging findings and to investigate the usefulness of this method in detecting active muscle disease in juvenile dermatomyositis and juvenile systemic lupus erythematosus patients. DESIGN: Transverse study, blinded assessment. SETTING: University referral unit (Pediatric Rheumatology section, Department of Pediatrics, Universidade Federal de São Paulo / Escola Paulista de Medicina). SAMPLE: Thirteen patients (9 girls) with dermatomyositis, as well as 13 patients (12 girls) with juvenile systemic lupus erythematosus and 10 normal children (5 girls), were enrolled in the study. MAIN MEASUREMENTS: Qualitative and quantitative analyses of gluteus maximus, quadriceps, adductors and flexors were performed and evaluated by two radiologists, blinded to all clinical information. Spin-echo in T1, DP, T2 and IR was used in all MRI images. RESULTS: The different muscle groups presented non-uniform involvement in the patients. The patients with dermatomyositis presented acute and chronic muscular alterations, while those with lupus presented only chronic myopathy, especially atrophy. In the dermatomyositis group, the major alterations were found in the gluteus and flexor regions (signal intensity and fat replacement). The signal intensity was increased in all acute myopathies. CONCLUSION: The qualitative and quantitative resonance analyses are useful in detecting clinically active disease in patients with dermatomyositis.